Hubungan Perilaku Ibu dalam Pemberian Makan dan Tingkat Kecukupan Energi-Protein dengan Status Gizi Batita Usia 12-36 Bulan di Wilayah Kerja Puskesmas Tersono Kabupaten Batang - Yunaidah Yunaidah; Wiwik Wijaningsih (Poltekkes Kemenkes Semarang, 2013)
Background: The situation at the time of malnourished infants is the result of not giving enough food to meet nutrient in terms of quality and quantity. Less energi and protein in infants may hinder growth, especially vulnerable to diseases and infectious diseases lead to low levels of intelligence.Objectives: To know the relationship between maternal behavior in feeding and energy-sufficiency level of protein in the nutritional status of toddlers aged 12-36 months in the working area health center Tersono Batang regency. Method: The scope of this research is the field of nutritional science community with a location in the working area of Batang regency Tersono Health Center, the research conducted in October-December 2009, this kind of research through a descriptive analytic cross-sectional approach for the dependent and independent variables were collected at the same time. population is aged 12-36 months toddler of 1021, with the number of sample 100 toddlers.Detemination samples taken at random samples using interval sampling. Analysis of the relationship between maternal behavior in the feeding with nutritional status of toddlers aged 12-36 months, the level of energy and protein adequacy with nutritional status of toddlers 12-36 months of age using Chi-Square test. Results: Maternal behavior in the feeding a good of 63% and 37% less, the level of energy sufficiency for good 82% and 18% less, the level of protein adequacy for good 81% and less 19% and good nutritional status as many as 83% and 17% less.The relationship between maternal behavior in the feeding and level of adequacy of nutritional status of energy-protein are significantly ststistik .Conclusions: There is a relationship between maternal behavior in feeding and energy-sufficiency level of protein nutritional status. Suggestions: Suggestions to improve of information about the behavior of mothers in feeding to specially cleaning of toddlers and mothers.